The White Matter Rounds experience: The importance of a multidisciplinary network to accelerate the diagnostic process for adult patients with rare white matter disorders - Huang, Yu Tong; Giacomini, Paul S.; Massie, Rami; Venkateswaran, Sunita; Trudelle, Anne-Marie; Fadda, Giulia; Sharifian-Dorche, Maryam; Boudjani, Hayet; Poliquin-Lasnier, Laurence; Airas, Laura; Saveriano, Alexander W.; Ziller, Matthias Georg; et al. (Frontiers in Neurology, 2022)
Introduction. Adult genetic leukoencephalopathies present unique diagnostic challenges due to their overlap with common white matter diseases, notably multiple sclerosis (MS). In this context, collaborative networks contribute to shorten the diagnostic odyssey of patients and prevent misdiagnosis. The White Matter Rounds (WM Rounds) are multidisciplinary international online meetings attended by more than 30 physicians and scientists from 15 participating sites that gather monthly to discuss patients with atypical white matter disorders. We present the experience of the WM Rounds and their value in differentiating among white matter diseases. Methods. We retrospectively reviewed the demographic, clinical and radiological data of all the subjects presented at the WM Rounds since 2013. Results. Seventy-four patients (mean age 44.3) have been discussed. Based on the WM Rounds recommendations, a definite diagnosis was made in 36/69 (52.2%) patients for which information was retrospectively available . Of these diagnosed patients, 20 (55.6%) had a genetic disease, 8 (22.2%) had MS, 3 (8.3%) had both MS and a genetic disorder and 5 (13.9%) had other non-genetic conditions. The subjects who currently remain without a definite diagnosis have been recruited in research studies aimed at identifying novel forms of genetic MS mimickers. Conclusions. The experience of the WM Rounds Network demonstrates the benefit of collective discussions to increase the diagnostic rate in patients with atypical leukoencephalopathies. Networks of this nature allow physicians to share information on rare cases from across the world, provide a basis for multicenter research studies, and serve as model for other rare diseases.